The effects of pine mistletoe (Viscum album subsp. austriacum) on the growth of Scots pine and Crimean pine in Turkey - Sakici, Oytun Emre; Özcan, Gonca Ece; Seki, Mehmet; Sağlam, Fadime (Wiley, 2023)
AbstractIn this study, the effect of pine mistletoe (Viscum album subsp. austriacum) on basal area increment of Crimean pine and Scots pine was investigated. Dendrochronological data were collected from 223 (71 uninfected and 152 infected) Crimean pines and 195 (77 uninfected and 118 infected) Scots pines located in Kastamonu province of Turkey in 2014. Infected sample trees were classified as light, moderate or severe infection levels. Growth trends and basal area increment loses were compared between uninfected and infected trees for the periods of the last 10, 20 and 30 years. In addition, infection status of forest stands was investigated using temporary sample plots; 27 plots in Crimean pine stands and 26 plots in Scots pine. Results demonstrated that basal area increments were negatively affected by pine mistletoe for both species. Mean basal area increment losses of infected trees for the last decade were determined as 24% for Scots pine and 26% for Crimean pine. Basal area increment losses varied by infection levels (light, moderate and severe) as follows: 25%, 20% and 28% for Scots pines and 20%, 32% and 9% for Crimean pines. Scots pine stands were more severely infected by pine mistletoe than Crimean pine stands. There were negative correlations between number of infected trees and stand density for both species, while positive correlation was detected between the number of infected trees and mean diameter for Scots pine. The results of this study indicate that the pine mistletoe infection has negative effect on radial growth of Scots pine and Crimean pine trees. The results can be an important contribution to the forest management and protection activities in mistletoe‐infected stands.
Keywords: 15. Life on land